Optimal Timing of Mental Practice on Learning the Volleyball Service Skill - Mohsen Afrouzeh; Mehdi Sohrabi; Hamid Reza Taheri; Ali Afroozeh (Annals of Applied Sport Science, 2013)
The goal of this study is searching effective time (before, during and after physical practice) for mental practice in learning the Volleyball Service Skill. Forty-five beginner students, aged 12–14 years, with no history of Volleyball Service Skill participated in the study (45 Male ones). Most of them were Secondary school students. All were unable to serve Volleyball correctly. The subjects were divided into the three groups (MP before PP, MP during PP and MP after PP). All subjects performed mental and physical practice in 21 sessions and for 30 minutes per session. The subjects were tested at the end of the 7th, 14th, 21th, and 28th sessions. The Volleyball Serving Test was used for test comparing the rate of learning. The result of this research showed there was significant difference between means of the MP-during-PP group, and the MP-before-PP and the MP-after-PP groups in improving their Volleyball Service skill. Moreover, the MP-before-PP and MP-after-PP groups did not differ from each other concerning the scores. The retention test showed that subjects in the MP-before-PP and the MP-after-PP groups, in contrast to the MP-during-PP group, did not significantly improve their Volleyball Service skill. This study suggested that coaches and P.E teachers apply mental practice (10 minutes) as an essential part in programs and teach the beginners that use mental practice in every time of physical practice (spatially during physical practice).